Solid secondary battery and method for producing coating liquid for forming intermediate layer of solid secondary battery
By configuring a low elastic modulus carbon, silicon particles and adhesive intermediate layer in a solid lithium secondary battery, the problem of output characteristics degradation caused by changes in the thickness of the negative electrode layer is solved, and an intermediate layer with high charge conductivity and stable shape is achieved, thereby improving battery performance.
Patent Information
- Application Number
- CN202510227544.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-30
- Filing Date
- 2025-02-27
- Publication Date
- 2025-09-30
AI Technical Summary
At high current density, the output characteristics of solid lithium secondary batteries decline, mainly due to the reduced adhesion between the negative electrode layer and the intermediate layer, which causes the thickness of the negative electrode layer to change during charging and discharging, affecting battery performance.
An intermediate layer containing carbon, silicon particles and a binder is arranged between the negative electrode layer and the solid electrolyte layer. The composite elastic modulus is below 200 MPa. By adjusting the ratio of each component and the stirring conditions, an intermediate layer with high charge medium mobility and low elastic modulus is formed.
The output characteristics of the solid secondary battery are improved, the negative electrode layer and the intermediate layer are ensured to be stable in a highly close state, and the charge conductivity and shape adaptability of the battery are enhanced.
Smart Images

Figure CN120728003A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid secondary battery and a method for producing a coating liquid for forming an intermediate layer of the solid secondary battery. Background Art
[0002] In recent years, research and development of secondary batteries, which contribute to energy efficiency, has been underway to ensure more people have access to affordable, reliable, sustainable, and advanced energy. Among secondary batteries, solid secondary batteries using solid electrolytes have attracted considerable attention due to their improved safety, resulting from their non-flammable nature, and their higher energy density.
[0003] Solid-state secondary batteries are batteries with a solid electrolyte layer placed between the positive and negative electrode layers. Known solid-state batteries include lithium ions as the charge transfer medium. In these solid-state lithium secondary batteries, to suppress uneven lithium deposition at the interface of the negative electrode layer, the placement of an intermediate layer containing carbon and metal nanoparticles between the negative electrode layer and the solid electrolyte layer has been explored (see Patent Document 1).
[0004] [Prior Art Literature]
[0005] (Patent Document)
[0006] Patent Document 1: International Publication No. 2023-189892 Summary of the Invention
[0007] [Problems to be solved by the invention]
[0008] Moreover, in the technology related to secondary batteries, one of the problems to be solved is to improve the output characteristics that can be discharged at a high current density. In order to improve the output characteristics of solid secondary batteries, an effective means is to configure a highly conductive intermediate layer of a charge transfer medium between the negative electrode layer and the solid electrolyte layer. However, in solid lithium secondary batteries, a battery with the following structure has been explored, wherein the structure uses lithium or a lithium alloy as the material of the negative electrode active material layer of the negative electrode layer, and when charging, lithium ions are precipitated on the surface of the negative electrode active material layer to form a lithium metal layer, and when discharging, the lithium ions released from the lithium metal layer are absorbed into the positive electrode. In a solid lithium secondary battery of this structure, sometimes, the change in the thickness of the negative electrode layer caused by charging and discharging will reduce the adhesion between the negative electrode layer and the intermediate layer, thereby reducing the output characteristics of the solid secondary battery.
[0009] The present invention has been made in view of the above-mentioned problems and aims to provide a solid secondary battery with improved output characteristics and a coating liquid for forming an intermediate layer capable of improving the output characteristics of the solid secondary battery, thereby contributing to improved energy efficiency.
[0010] [Technical means to solve the problem]
[0011] The present inventors have discovered that, in order to solve the above-mentioned problems, it is effective to use a layer formed from a composition containing carbon, silicon particles, and a binder so as to have a complex elastic modulus of 200 MPa or less as an intermediate layer, thereby completing the present invention. Accordingly, the present invention provides the following.
[0012] (1) A solid secondary battery comprising a positive electrode layer, a negative electrode layer, a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, and an intermediate layer disposed between the negative electrode layer and the solid electrolyte layer, wherein the intermediate layer comprises carbon, silicon particles, and a binder, and the composite elastic modulus of the intermediate layer is 200 MPa or less.
[0013] According to the solid secondary battery of (1), since the intermediate layer contains carbon, silicon particles and a binder, the conductivity of the charge medium transfer medium between the solid electrolyte and the negative electrode becomes higher. In addition, since the composite elastic modulus of the intermediate layer is as low as 200 MPa or less, the shape is easily deformed. Therefore, even if the negative electrode active material layer contains lithium or a lithium alloy, the thickness of the negative electrode layer changes due to charging and discharging, and the negative electrode layer and the intermediate layer will be stabilized in a highly sealed state. As a result, the output characteristics of the solid secondary battery are improved.
[0014] (2) A solid secondary battery according to (1), wherein, relative to the total amount of the carbon, the silicon particles and the binder, the carbon content is in the range of 50% by mass or more and 90% by mass or less, the silicon particle content is in the range of 7% by mass or more and 45% by mass or less, and the binder content is in the range of 3% by mass or more and 8% by mass or less.
[0015] According to the solid secondary battery of (2), since the contents of carbon, silicon particles, and the binder in the intermediate layer are within the above-mentioned ranges, the conductivity of the charge transfer medium in the intermediate layer is high and the complex elastic modulus is low.
[0016] (3) The solid secondary battery according to (2), wherein the content of the binder is within a range of 3 mass % to 4 mass %.
[0017] According to the solid secondary battery of (3), since the content of the binder is within the above-mentioned range, the conductivity of the charge transfer medium in the intermediate layer becomes higher.
[0018] (4) The solid secondary battery according to (2) or (3), wherein a ratio of the content of the silicon particles to the content of the carbon is within a range of 0.30 to 0.35.
[0019] According to the solid secondary battery of (4), since the ratio of the content of silicon particles to the content of carbon is within the above range, the conductivity of the charge transfer medium in the intermediate layer becomes higher.
[0020] (5) The solid secondary battery according to any one of (1) to (4), wherein the carbon has a BET specific surface area of 50 m 2 / g and above 80 m 2 / g or less of carbon black.
[0021] According to the solid secondary battery of (5), by bonding the carbon black having a high specific surface area to the silicon particles using a binder, the conductivity of the charge medium transfer medium in the intermediate layer becomes higher and the complex elastic modulus becomes lower.
[0022] (6) The solid secondary battery according to any one of (1) to (5), wherein the intermediate layer has a complex elastic modulus of 80 MPa or less.
[0023] According to the solid secondary battery of (6), since the complex elastic modulus is as low as 80 MPa or less, the shape is further deformed, so even if the negative electrode layer is deformed, the negative electrode layer and the intermediate layer are stabilized in a state of further close contact.
[0024] (7) A method for producing a coating liquid for forming an intermediate layer of a solid secondary battery, comprising mixing a silicon particle dispersion, carbon, and a binder, wherein the silicon particle dispersion is obtained by stirring silicon particles in a solvent at a peripheral speed of not less than 20 m / s and not more than 40 m / s for not less than 60 seconds.
[0025] According to the method for producing a coating liquid for forming an intermediate layer of a solid secondary battery described in (7), a coating liquid in which silicon particles are dispersed in the form of primary particles or fine aggregated particles close to primary particles can be obtained industrially advantageously. Furthermore, by using this coating liquid, an intermediate layer can be formed that has high conductivity as a charge transfer medium, a low complex elastic modulus, and is easily deformable.
[0026] (Effects of the Invention)
[0027] According to the present invention, it is possible to provide a solid secondary battery having improved output characteristics and a coating liquid for forming an intermediate layer capable of improving the output characteristics of the solid secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic cross-sectional view of a solid secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION
[0029] Hereinafter, embodiments of the present invention will be described with reference to the drawings. However, the embodiments shown below are for illustrative purposes only and are not intended to limit the present invention.
[0030] Figure 1 Schematic cross-sectional view of a solid secondary battery according to one embodiment of the present invention. Figure 1 As schematically shown in , the solid secondary battery 1 of this embodiment includes a positive electrode layer 10 , a negative electrode layer 20 , a solid electrolyte layer 30 disposed between the positive electrode layer 10 and the negative electrode layer 20 , and an intermediate layer 40 disposed between the negative electrode layer 20 and the solid electrolyte layer 30 .
[0031] The positive electrode layer 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 laminated on the surface of the positive electrode current collector 11. Examples of the material of the positive electrode current collector 11 include aluminum, aluminum alloys, stainless steel, nickel, iron, and titanium.
[0032] The positive electrode active material layer 12 contains a positive electrode active material. The positive electrode active material is a lithium compound that releases lithium ions during discharge and absorbs lithium ions during charge. As the lithium compound, for example, a layered active material, a spinel type active material, an olivine type active material can be used. Specific examples of positive electrode active materials include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium nickel manganese cobalt oxide (NMC: LiNi p Mn q Co r O2(p+q+r=1), LiNi p Al q Co r O2 (p + q + r = 1), lithium manganate (LiMn2O4), Li 1+x Mn 2-x-y Examples include heterogeneous element-substituted Li-Mn spinel represented by MO4 (x+y=2, M selected from at least one of Al, Mg, Co, Fe, Ni, and Zn), lithium titanate (an oxide containing Li and Ti), and lithium metal phosphate (LiMPO4, M selected from at least one of Fe, Mn, Co, and Ni). The positive electrode active material layer 12 may further include a solid electrolyte, a conductive additive, and a binder.
[0033] The negative electrode layer 20 includes a negative electrode current collector 21 and a negative electrode active material layer 22 laminated on the surface of the negative electrode current collector 21. Examples of the material of the negative electrode current collector 21 include copper, copper alloys, nickel, and stainless steel.
[0034] As the negative electrode active material contained in the negative electrode active material layer 22, a known material that can absorb lithium ions during charging and release lithium ions during discharge can be appropriately selected. As the negative electrode active material, for example, metals such as lithium metal and lithium alloys, lithium transition metal oxides such as lithium titanate, transition metal oxides such as TiO2, Nb2O3 and WO3, Si, SiO, metal sulfides, metal nitrides, and carbon materials such as artificial graphite, natural graphite, graphite, soft carbon and hard carbon can be used. Examples of metals contained in lithium alloys include Mg, Si, Au, Ag, In, Ge, Sn, Pb, Al and Zn. The negative electrode active material layer 22 may also include a solid electrolyte, a conductive additive, and a binder.
[0035] The solid electrolyte layer 30 includes a solid electrolyte. As examples of solid electrolytes, sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes can be used. Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, etc. The sulfide solid electrolyte may also have an argyrodite-type crystal structure. Examples of oxide solid electrolytes include sodium superionic conductor (NASICON) type oxides, garnet-type oxides, and perovskite-type oxides. Examples of NASICON-type oxides include oxides containing Li, Al, Ti, P, and O (e.g., Li 1.5 Al 0.5 Ti 1.5 (PO4)3). Examples of garnet-type oxides include oxides containing Li, La, Zr, and O (e.g., Li7La3Zr2O 12 Examples of perovskite-type oxides include oxides containing Li, La, Ti, and O (eg, LiLaTiO 3 ).
[0036] Intermediate layer 40 includes carbon, silicon particles, and a binder. Intermediate layer 40 may also be formed solely from carbon, silicon particles, and a binder. The carbon content relative to the total amount of carbon, silicon particles, and binder may be, for example, in the range of 50% by mass to 90% by mass, or in the range of 60% by mass to 80% by mass. The silicon particle content may be, for example, in the range of 7% by mass to 45% by mass, or in the range of 10% by mass to 40% by mass. The binder content may be in the range of 3% by mass to 8% by mass, or in the range of 3% by mass to 4% by mass. The ratio of the silicon particle content to the carbon content (silicon particles / carbon) may be in the range of 0.30 to 0.35.
[0037] The intermediate layer 40 has a composite elastic modulus of 200 MPa or less. The intermediate layer 40 has a low composite elastic modulus and is easily deformed. For example, even if the thickness of the negative electrode layer 20 changes, the intermediate layer 40 will deform according to the change. Therefore, the intermediate layer 40 and the negative electrode layer 20 are stabilized in a highly adhered state. Therefore, the output characteristics of the solid secondary battery 1 of this embodiment are improved. The composite elastic modulus of the intermediate layer 40 can be 150 MPa or less, 100 MPa or less, or 80 MPa or less. From the perspective of maintaining the shape of the intermediate layer 40, the composite elastic modulus of the intermediate layer 40 can also be 10 MPa or more.
[0038] The carbon contained in the intermediate layer 40 may be amorphous carbon. Examples of amorphous carbon include carbon blacks such as acetylene black, furnace black, and Ketjen black, coke, and activated carbon. Amorphous carbon may be easily graphitized carbon (soft carbon), hardly graphitized carbon (hard carbon), carbon nanotubes (CNTs), fullerenes, or graphene.
[0039] The carbon contained in the intermediate layer 40 is preferably carbon black, more preferably carbon black having a BET specific surface area of, for example, 50 m 2 / g and above 80 m 2 By binding the carbon black with a high specific surface area to the silicon particles with a binder, an intermediate layer 40 with high lithium ion conductivity and low complex elastic modulus can be obtained.
[0040] Examples of the binder contained in the intermediate layer 40 include acrylic polymers, cellulose polymers, styrene polymers, vinyl acetate polymers, urethane polymers, vinyl fluoride polymers, and polyvinylidene fluoride (PVDF) polymers.
[0041] The intermediate layer 40 can be formed, for example, by a coating method. The coating method is a method of applying a coating liquid for forming the intermediate layer containing the material of the intermediate layer 40 and drying the coating liquid.
[0042] As a method for producing a coating liquid for forming an intermediate layer, for example, a method can be used in which a silicon particle dispersion, obtained by stirring silicon particles in a solvent at a peripheral speed of not less than 20 m / s and not more than 40 m / s for not less than 60 seconds, carbon, and a binder are mixed. The silicon particle dispersion may be obtained by stirring silicon particles in a solvent at a peripheral speed of not less than 20 m / s and not more than 40 m / s for not less than 60 seconds. The silicon particles may be dispersed in the silicon particle dispersion as primary particles or fine agglomerated particles close to primary particles. A high-speed stirrer can be used as a stirring device for dispersing the silicon particles.
[0043] The solid secondary battery 1 is formed by combining a positive electrode layer 10, a solid electrolyte layer 30, an intermediate layer 40 and a negative electrode layer 20. Figure 1 In addition, after the above stacking, it can also be pressed to integrate. Figure 1 A plurality of the structural units shown are stacked as unit cells.
[0044] According to the solid secondary battery 1 of this embodiment, constructed as described above, the intermediate layer 40 contains carbon, silicon particles, and a binder, resulting in enhanced conductivity as a charge transfer medium between the solid electrolyte and the negative electrode. Furthermore, since the intermediate layer 40 has a low composite elastic modulus of less than 200 MPa and is easily deformable, even if the negative electrode active material layer 22 contains lithium or a lithium alloy and the thickness of the negative electrode layer 20 changes due to charge and discharge, the negative electrode layer 20 and the intermediate layer 40 remain in a stable, highly adherent state. Consequently, the output characteristics of the solid secondary battery 1 are improved.
[0045] The method for producing a coating liquid for forming an intermediate layer of a solid secondary battery according to this embodiment provides an industrially advantageous method for obtaining a coating liquid containing silicon particles dispersed in the form of primary particles or fine aggregated particles close to primary particles. Furthermore, the use of this coating liquid enables the formation of an intermediate layer 40 having high conductivity, a low complex elastic modulus, and easily deformable shape, as a charge transfer medium.
[0046] [Example]
[0047] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to these Examples.
[0048] <Example 1>
[0049] [Preparation of coating liquid for forming intermediate layer]
[0050] 5 parts by mass of silicon particles were added to NMP (N-methyl-2-pyrrolidone) and stirred using a high-speed stirrer (FILMIX, manufactured by Primix Co., Ltd.) at a stirring speed of 30 m / s and a stirring time of 150 seconds to prepare a silicon particle dispersion. Subsequently, 71 parts by mass of carbon A (BET specific surface area 62 m 2 / g of carbon black) and 5 parts by mass of a PVDF-based binder were stirred and mixed using a high-speed stirrer (FILMIX, manufactured by Primix Co., Ltd.). In this way, a coating liquid for forming an intermediate layer was prepared.
[0051] [Fabrication of Intermediate Layer / Particle-Like Solid Electrolyte Base Material / Intermediate Layer Laminate]
[0052] An argyrodite-type sulfide solid electrolyte was press-formed to produce a granular solid electrolyte substrate with flat upper and lower surfaces. An intermediate layer coating solution was applied to each of the upper and lower surfaces of the resulting solid electrolyte substrate and dried to produce an intermediate layer / granular solid electrolyte substrate / intermediate layer laminate.
[0053] [evaluate]
[0054] (Determination of complex elastic modulus)
[0055] The complex elastic modulus of one of the obtained intermediate layers was measured, and the results are shown in Table 1 below.
[0056] (Determination of limiting current density)
[0057] A stacked electrode was fabricated by laminating a metallic lithium foil on one surface of a copper foil. The metallic lithium foil of the stacked electrode was superimposed on the respective surfaces of the intermediate layer, solid electrolyte layer, and intermediate layer stack, creating an evaluation unit consisting of the stacked electrode / intermediate layer / granular solid electrolyte substrate / intermediate layer / stacked electrode. The limiting current density of the resulting evaluation unit was measured. The results are shown in Table 1 below.
[0058] <Examples 2 to 4, Comparative Example 1>
[0059] In the preparation of the coating liquid for forming the intermediate layer, the same method as in Example 1 was used except that the type of carbon, the amounts of carbon, silicon particles, and the binder, and the dispersion conditions of the silicon particles were changed to the conditions described in Table 1 below. Carbon A has a BET specific surface area of 62 m 2 / g of carbon black, carbon B has a BET specific surface area of 39 m 2 / g of carbon black. Using the obtained coating solution for forming an intermediate layer, an intermediate layer / granular solid electrolyte substrate / intermediate layer laminate was produced in the same manner as in Example 1, and the complex elastic modulus and limiting current density were measured. The results are shown in Table 1 below.
[0060] [Table 1]
[0061]
[0062] The results of Examples 1 to 4 shown in Table 1 indicate that, according to the present invention, an intermediate layer having a composite elastic modulus of 200 MPa or less can be obtained by using an intermediate layer-forming coating solution obtained by mixing a silicon particle dispersion containing dispersed silicon particles, carbon, and a binder. Furthermore, it can be seen that the evaluation cells using this intermediate layer exhibited a high limiting current density, thereby improving the output characteristics of the solid secondary battery using this intermediate layer. On the other hand, the evaluation cells using an intermediate layer made from the silicon particle dispersion of Comparative Example 1, where the silicon particles had a short dispersion time, exhibited a lower limiting current density.
[0063] Reference numerals
[0064] 1 Solid secondary battery
[0065] 10. Positive electrode layer
[0066] 11. Positive electrode collector
[0067] 12. Positive electrode active material layer
[0068] 20 negative electrode layer
[0069] 21. Negative electrode current collector
[0070] 22 Negative electrode active material layer
[0071] 30 Solid electrolyte layer
[0072] 40 middle layer
Claims
1. A solid secondary battery comprising a positive electrode layer, a negative electrode layer, a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, and an intermediate layer disposed between the negative electrode layer and the solid electrolyte layer. The intermediate layer comprises carbon, silicon particles and a binder. The intermediate layer has a complex elastic modulus of 200 MPa or less.
2. The solid secondary battery according to claim 1, wherein Relative to the total amount of the aforementioned carbon, the aforementioned silicon particles and the aforementioned binder, the content of the aforementioned carbon is in the range of not less than 50 mass % and not more than 90 mass %, the content of the aforementioned silicon particles is in the range of not less than 7 mass % and not more than 45 mass %, and the content of the aforementioned binder is in the range of not less than 3 mass % and not more than 8 mass %.
3. The solid secondary battery according to claim 2, wherein The content of the binder is within a range of 3% by mass or more and 4% by mass or less.
4. The solid secondary battery according to claim 2 or 3, wherein The ratio of the content of the silicon particles to the content of the carbon is within a range of 0.30 to 0.
35.
5. The solid secondary battery according to claim 1 or 2, wherein The carbon has a BET surface area of 50 m 2 / g and above 80 m 2 / g or less of carbon black.
6. The solid secondary battery according to claim 1 or 2, wherein: The intermediate layer has a complex elastic modulus of 80 MPa or less.
7. A method for producing a coating liquid for forming an intermediate layer of a solid secondary battery, comprising mixing a silicon particle dispersion, carbon, and a binder, wherein the silicon particle dispersion is obtained by stirring silicon particles in a solvent at a peripheral velocity of not less than 20 m / s and not more than 40 m / s for not less than 60 seconds.
Citation Information
Patent Citations
Solid-state secondary battery
WO2023189892A1